2017
DOI: 10.1177/1948550617707017
|View full text |Cite
|
Sign up to set email alerts
|

Social Distance Increases Perceived Physical Distance

Abstract: Proximity, or spatial closeness, can generate social closeness—the closer people are together, the more they interact, affiliate, and befriend one another. Mediated communication allows people to bridge spatial distance and can increase social closeness between conversational partners, even when they are separated by distance. However, mediated communication may not always make people feel closer together. Here, we test a hypothesis derived from construal theory, about one way in which mediated communication m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…Regarding the ratings of perceived physical distance, previous research has shown that it can be affected by a number of factors, such as perceived social distance (Won et al, 2018), social exclusion (Knowles et al, 2014;Pitts et al, 2014), motivation and desire (Balcetis and Dunning, 2010), as well as perceived threat (Cole et al, 2013). The pandemic has drastically changed our relationship with physical proximity, by associating it to the threat of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ratings of perceived physical distance, previous research has shown that it can be affected by a number of factors, such as perceived social distance (Won et al, 2018), social exclusion (Knowles et al, 2014;Pitts et al, 2014), motivation and desire (Balcetis and Dunning, 2010), as well as perceived threat (Cole et al, 2013). The pandemic has drastically changed our relationship with physical proximity, by associating it to the threat of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous work on social closeness through mediated interactions [59], we asked 10 questions on liking, affiliation, and connectedness ( alpha = 0.92). We took the average of 10 social closeness questions for each individual and then took the average of both participants’ scores to create a group social closeness measure ( M = 3.429, SD = 0.586).…”
Section: Methodsmentioning
confidence: 99%
“…As described before, self-disclosure can be used to develop closeness in a relationship; see also research on the experimental generation of interpersonal closeness [35,36]. By communicating in a warm way with distant others, distance can be bridged and perceived closeness increased [37]. On the other hand, if individuals decide to not share or to even actively hide information, they might create (physical) distance between themselves and other persons by avoiding to meet them [34].…”
Section: Would the Disclosure Of Secrets Impact Social Distance?mentioning
confidence: 99%